Impact of Belimumab on Organ Damage in Systemic Lupus Erythematosus. Issue 11 (4th August 2022) - Urowitz, Murray B.; Aranow, Cynthia; Asukai, Yumi; Bass, Damon L.; Bruce, Ian N.; Chauhan, Deven; Dall'Era, Maria; Furie, Richard; Fox, Norma Lynn; Gilbride, Jennifer A.; Hammer, Anne; Ginzler, Ellen M.; et al.
Abstract : Organ damage is a key determinant of poor long‐term prognosis and early death in patients with systemic lupus erythematosus (SLE). Prevention of damage is a key treatment goal of the 2019 update of the European Alliance of Associations for Rheumatology (EULAR) recommendations for SLE management. Belimumab is a monoclonal antibody that inhibits B lymphocyte stimulator (BLyS) and is the only therapy approved for both SLE and lupus nephritis. Here, we review the clinical trial and real‐world data on the effects of belimumab on organ damage in adult patients with SLE. Across 4 phase III studies, belimumab in combination with background SLE therapy demonstrated consistent reductions in key drivers of organ damage including disease activity, risk of new severe flares, and glucocorticoid exposure compared to background therapy alone. Long‐term belimumab use in SLE also reduced organ damage progression measured by the Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index, as reported in open‐label extension studies, and propensity score–matched comparative analyses to background therapy alone. Results from a clinical trial showed that in patients with active lupus nephritis, belimumab treatment improved renal response, reduced the risk of renal‐related events, and impacted features related to kidney damage progression compared to background therapy alone. The decrease of organ damage accumulation observed with belimumab treatment in SLE, including lupus nephritis, suggest a disease‐modifying effect.